INFORMATION SYSTEMS DEVELOPMENT PLAN FOR OK ROOMS INN (PANABO BRANCH) - Jenerica N. Marquez; Michelle Laurente; Archie B. Matuguina; Marjorie M. Orig; Glendell R. Jadraque (International Journal of Innovations in Engineering Research and Technology, 2021)
OK Rooms Inn, Panabo City branch specifically, is a three-year-old lodging business for travellers, tourists, and even locals seeking an excellent place to stay in Barangay Gredu, Panabo City. OK Rooms Inn offers two different variations of room accommodations which are the Regular Room and VIP Room. In reference to it, the study will explain the current business flow and of the Inn as well as the business’s background, specific stakeholders and determine particular concerns and problems that the company has encountered through an interview. This research will propose a Customer Relationship Management System, which focuses on implementing a database system. The study will state its possible effects and the advantages it can offer to the business itself. Recommendations and ideas for a better workflow of the company, management, value creation, and decision-making will coincide with an efficient, time-relevant, and executable Development Plan for the OK Rooms Inn is on the list. This is to help and address spotted problems of the Inn and help them foster their services while saving time and effort at the same time.